From Achilles’s Tent to a San Francisco Restaurant: Imaginations of the Closet in Thom Gunn’s Poetry - Horváth, Imre Olivér (Hungarian Journal of English and American Studies, 2020)
This essay examines Thom Gunn’s key poems, chronologically mapping Ruth E. Fassinger’s model of gay and lesbian identity development onto it. Gunn’s poetry gradually changed in terms of how he addressed his homosexuality: whereas in his early work his sexual orientation was concealed, later it became increasingly visible, to the point of unambiguously referring to himself as “queer” in a poem from the 1980s. The poems discussed in this article—“The Wound” (1954), “The Secret Sharer” (1954), “The Corridor” (1957), “The Monster” (1961), “Bravery” (1967), “Behind the Mirror” (1976), and “Talbot Road” (1982)—address the split self of the speaker accompanied by spatial division. The poems with this leitmotif form a corpus characterized by a gradual change in terms of the rigidity of the division. Identifying the spatial division as the closet and the split self as the closeted subject, the article argues that Gunn’s coming out of the closet is a recurring poetic device deliberately developed throughout his oeuvre, which demonstrates his growth as an artist. (IOH)